2011
DOI: 10.1056/nejmoa1011802
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disability 5 Years after Acute Respiratory Distress Syndrome

Abstract: Exercise limitation, physical and psychological sequelae, decreased physical quality of life, and increased costs and use of health care services are important legacies of severe lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

69
1,787
15
107

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,388 publications
(1,978 citation statements)
references
References 75 publications
69
1,787
15
107
Order By: Relevance
“…First, the authors provide valuable, objective data to further support the persistence of physical limitation after critical illness months after the resolution of the aggressive and relentless muscle proteolysis documented in recent studies [5]; similar data have been reported in survivors of acute lung injury even 5 years after hospital discharge [6]. Second, they confirm that severe sepsis is an important cause of long-lasting physical dysfunction and muscle weakness after acute illness, as suggested by a recent official American Thoracic Society clinical practice guideline [7].…”
supporting
confidence: 59%
“…First, the authors provide valuable, objective data to further support the persistence of physical limitation after critical illness months after the resolution of the aggressive and relentless muscle proteolysis documented in recent studies [5]; similar data have been reported in survivors of acute lung injury even 5 years after hospital discharge [6]. Second, they confirm that severe sepsis is an important cause of long-lasting physical dysfunction and muscle weakness after acute illness, as suggested by a recent official American Thoracic Society clinical practice guideline [7].…”
supporting
confidence: 59%
“…2 However, both syndromes continue to be associated with high mortality and morbidity. 3,4 Despite decades of clinical trials, eff ective pharmacotherapy for either syndrome remains elusive. 5,6 A growing body of evidence suggests that cell-based therapy with stem or progenitor cells holds substantial therapeutic promise for a host of infl ammatory disorders, including ARDS and sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have argued that critical illnesses and their associated treatment-related exposures may have a causal role in increasing the risk of subsequent depression; 913 these studies have motivated an NIH-funded randomized controlled trial of empiric escitalopram for patients undergoing mechanical ventilation (ClinicalTrials.gov identifier: NCT00872027). However, very few studies of post-critical illness depression are appropriately designed to test this hypothesis – only two have examined the contribution of premorbid depression using a standardized measure, 14,15 of which only one examined pre-critical illness depressive symptoms prospectively in a small sample of critical illness survivors.…”
Section: Introductionmentioning
confidence: 99%